1989
DOI: 10.1159/000185295
|View full text |Cite
|
Sign up to set email alerts
|

Adult T Cell Leukemia in Hemodialysis Patients from the Kagoshima District, an Area in Which Human T Cell Leukemia Virus Type I Is Highly Endemic

Abstract: We report 2 cases of adult T cell leukemia (ATL) from hemodialysis (HD) patients with chronic renal failure (CRF) in the Kagoshima district, an endemic area of human T cell leukemia virus type I(HTLV-I) in Japan. The positivity of antibodies to ATL-associated antigen(anti-ATLA) in HD patients, regardless of whether or not blood transfusions were given, has been higher than in healthy persons in the district (p < 0.01). ATL is considered to break out from HTLV-I carriers. Further study should be conducted to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In Japan, increased adult T-cell leukemias are also described in MHD patients due to an activation of oncogenic human T-cell leukemia virus type I [54].…”
Section: Chronic Infections and Inflammationsmentioning
confidence: 99%
“…In Japan, increased adult T-cell leukemias are also described in MHD patients due to an activation of oncogenic human T-cell leukemia virus type I [54].…”
Section: Chronic Infections and Inflammationsmentioning
confidence: 99%
“…Several studies, especially from Japan and Iran, have found high rates of HTLV‐1 infection ranging from 6.7% to 21.2% among people with CKD . To date, no study has reported renal disease among people with HTLV‐1 in the Caribbean and south America, two other major HTLV‐1 endemic areas.…”
Section: Discussionmentioning
confidence: 94%
“…Limited evidence suggests that HTLV‐1a infection might be associated with CKD. When compared with controls without CKD, higher HTLV‐1 seropositivity rates were observed among haemodialysis (HD) patients, and those with histologically confirmed primary glomerulonephritis . However, only one study measured HTLV‐1a PVL, which were higher among CKD cases .…”
Section: Introductionmentioning
confidence: 99%
“…The routine administration of blood products to CKD5 patients at a time when blood donations were not screened for HTLV-1 complicates the interpretation of earlier studies. [26][27][28] However, blood donors have been tested for HTLV-1 in Japan, Australia, and Iran since 1986, 29 1993, 32 and 1995, 33 respectively, making HTLV-1 transmission by blood transfusion unlikely in recent studies. We previously found a significantly higher HTLV-1 PVL among cases with CKD5 relative to controls without CKD 30 which suggests a potential mechanism for renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Limited epidemiological evidence supports an association between HTLV‐1 infection and CKD. In HTLV‐1 endemic areas in Iran and Japan, HTLV‐1 seropositivity rates are higher among patients receiving renal replacement therapy than those without CKD 23–28 . Interpreting earlier studies 26–28 is rendered difficult by the routine administration of blood transfusions to patients with CKD stage 5 (CKD5) before the introduction of HTLV‐1 testing of blood donors 29 .…”
Section: Introductionmentioning
confidence: 99%